The development and validation of a collective occupational identity construct (COIC) in a natural resource context. (August 2015) - Groth, Theresa M.; Curtis, Allan; Mendham, Emily; Toman, Eric
Abstract: The trend to multifunctional rural landscapes in developed economies is characterised by the contrasting values, land uses and land management practices of rural property owners. In agricultural regions, it seems these trends are, at least in part, an expression of the extent rural landholders identify as farmers. Investigation of these trends has been hampered by the absence of robust approaches to measuring occupational identity amongst rural landholders. Research discussed in this paper addresses that gap. The objective was to develop a valid, reliable and efficient measure of occupational identity. We did that using the collective identity construct (CIC) and adapted a widely accepted 17-item CIC scale to explore the extent rural landholders in south eastern Australia held a farmer identity. Drawing on a survey of 1900 rural landholders we assessed the reliability, validity and utility of that scale. Those tests resulted in a 12-item scale that we suggest provides a valid and reliable measure of occupational identity that can be applied in natural resource management contexts. Highlights: Rural areas are transitioning towards multifunctional landscapes. Rural transition research requires more focus on landowner occupational identity. Rural areas characterised by landowners' values, land uses, and management practices. The collective occupational identity construct provides a valid, reliable measure. The COIC can distinguish between landowners with differing levels of farmer identity.